Comparative study of the granulometric composition of seed materials used during the lactose crystallization - I. A. Evdokimov; I. K. Kulikova; A. S. Gridin; D. S. Khazov; L. A. Gordienko (Современная наука и инновации)
The properties of many dairy products with high levels of dry matter and lactose directly depend on the crystallization of lactose, which is a key component. To control these properties and achieve the desired parameters, the process of lactose crystallization is often used. In this paper, data on the granulometric composition of seeding materials used to manage the lactose crystallization process in dairy raw materials are presented. Measurements of particle sizes are performed by laser diffraction on microcrystalline lactose, powdered sugar, and a liquid crystallizer based on sucrose. It was found that the seeding materials have different particle sizes. The liquid crystallizer is distinguished by its greater uniformity and convenience of dosing, but its use does not significantly affect the crystallization rate.